Incumbency Advantages: Price Dispersion, Price Discrimination and Consumer Search at Online Platforms - Gugler, Klaus; Heim, Sven; Janssen, Maarten; Liebensteiner, Mario (Journal of Political Economy Microeconomics, 2023)
When firms can make certain prices only available to consumers who search for lower prices, they can price discriminate between consumers with lower and higher search costs. We study one such an environment. Consumers in local German electricity retail markets pay the baseline tariff of their incumbent if they do not search. To observe prices of other firms, they can access an online platform where the incumbent may also post another tariff. Pricing and search patterns differ substantially across local markets. Using panel data, we show that in local markets where more consumers search, incumbents have higher baseline tariffs, while online tariffs of the incumbents and entrants are lower. In a theoretical model, we discuss under which conditions an incumbent has an incentive to further differentiate its tariffs with more consumer search and whether regulators should consider banning such price discrimination practices.<br
Keywords: Search; Price Dispersion; Price Discrimination; Electricity